Students’ digital literacy on chemistry–STEAM project-based learning: a gender perspective - Nisa, Fakhira Ainun; Bahriah, Evi Sapinatul; Suryaningsih, Siti (IAIN Palangka Raya, 2024)
This study aims to analyze students' digital literacy in STEAM project-based chemistry learning based on a gender perspective. This study uses a quantitative descriptive method with data collection techniques through a questionnaire instrument on 30 students of class XI science who were selected by purposive sampling. The research instrument consisted of 6 indicators, which were developed into 18 questionnaire items, which were arranged using a Likert scale. Research data were analyzed quantitatively descriptively by calculating scores and percentages. The results of the analysis of students' digital literacy data as a whole showed an average of 81.75% in the excellent category. The study based on gender showed an average gain of 81% for female students and 82.6% for male students, both of which did not have a significant difference, and both were in the excellent category. These results indicate that the STEAM project approach can be an alternative learning that can maximize students' digital literacy.